2020
DOI: 10.1016/j.ijid.2020.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 25 death cases with COVID-19: A retrospective review of medical records in a single medical center, Wuhan, China

Abstract: This study aims to summarize the clinical characteristics of death cases with COVID-19 and to identify critically ill patients of COVID-19 early and reduce their mortality. Methods: The clinical records, laboratory findings and radiological assessments included chest X-ray or computed tomography were extracted from electronic medical records of 25 died patients with COVID-19 in Renmin Hospital of Wuhan University from Jan 14 to Feb 13, 2020. Two experienced clinicians reviewed and abstracted the data. Results:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
339
3
21

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 359 publications
(402 citation statements)
references
References 11 publications
26
339
3
21
Order By: Relevance
“…Respiratory failure or multiple organ failure is the direct cause of death in patients with COVID-19, and SBIs play an important role in this process [16]. Among the 1495 patients with COVID-19, the incidence of SBIs was 6.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory failure or multiple organ failure is the direct cause of death in patients with COVID-19, and SBIs play an important role in this process [16]. Among the 1495 patients with COVID-19, the incidence of SBIs was 6.8%.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer has a very high sensitivity for thrombotic disease, but its specificity is poor. Various studies in patients with COVID-19 have consistently shown a very strong association between increased D-dimer levels and severe disease/poor prognosis (Table 1) (7,11,(13)(14)(15)(16)(17).…”
Section: D-dimermentioning
confidence: 98%
“…reported similar ndings, indicating the potential critical condition and serious disturbance of internal environment in those severe infected cases [15]. Li et al found that some death cases of COVID-19 have superimposed bacterial pneumonia [16]. Bacterial infection leads to signi cant increased leucocyte count and neutrophil count.…”
Section: Relationship Between Recovery Of Eosinophil Count and Patienmentioning
confidence: 75%